Analysis of consumer behavior on purchasing decisions using q-ris as digital money at stationary Toko Merdeka in Pekanbaru - Rusaidi Thahery; Gusnafitri; Dewi Martha (Jurnal Mantik, 2024)
The use of retail is one of the business opportunities that offers various types of goods and services from hundreds of brands on the market. The competition of each product offered impacts consumers to open opportunities in choosing product variants. To support the interest of potential consumers in shopping, the choice of product variants offered must be of high quality at competitive prices. This study aims to determine the influence of cultural, social, personal, and psychological factors on consumer behavior at Toko Merdeka Stationary. This type of research uses a quantitative approach. Data was collected by taking population samples by purposive sampling in the Pekanbaru city area. Data was obtained from questionnaires distributed to 120 respondents who qualified for a sample of 114. The results of the study obtained: (1). Personal and psychological factors have a significant positive effect on purchasing decisions; (2) Cultural factors do not influence purchasing decisions; (3). Social factors are not worthy of being a tool for determining variables, because the directional patterns of such variables are inconsistent.